Assessing the substrate specificity of a micropollutant degrading strain: generalist or specialist?. Issue 11 (12th October 2022) - Schittich, Anna-Ricarda; McKnight, Ursula S.; Stedmon, Colin; Smets, Barth F.
Abstract : An organic micropollutant (OMP) degrader's ability to metabolize and compete for dissolved organic matter constituents might support its survival in natural aquatic environments. Abstract : Natural dissolved organic matter (DOM) can serve as an additional substrate for organic micropollutant (OMP) degrading bacteria, thus influencing OMP biodegradation in aquatic systems. DOM biodegradation depends on the OMP degrader's ability to grow on different DOM constituents, and on its capability to compete for DOM constituents against the rest of the resident aquatic microbial community. This study aimed to investigate the growth of a model OMP degrader strain, Novosphingobium sp. KN65.2 (assumed specialist), isolated for its ability to mineralize carbofuran, on thirteen DOM constituents; compare its metabolic capabilities to those of a common freshwater strain ( Pseudomonas fluorescens sp. P17) (generalist); and to evaluate competition for specific compounds. Growth experiments were carried out in pure- and mixed culture batch experiments. The DOM constituents tested included aromatic amino acids and a range of phenolic acids (lignin derivatives). The OMP degrader could biodegrade approximately half of the tested compounds. It showed a high specialization for substrates containing a hydroxyl-group in the para -position of the primary aromatic ring substituent. However, its broad substrate range enabled the strain to grow on the same number of auxiliary substrates as the generalist. Moreover, the OMP degrader was able to successfully compete against the generalist for the biodegradation of one (4-hydroxybenzaldehyde) out of three substrates (4-hydroxybenzoic acid, 4-hydroxybenzaldehyde, l -tyrosine), which were biodegraded by both strains. The study results provide insight on the substrate specificity of a model OMP degrader, which can inform development of modeling frameworks investigating the influence of DOM on OMP biodegradation.